Blended learning for doctoral training in the context of the COVID-19 pandemic - Simon, Yessy Villavicencio; Grajales Melian, Ivan Gabriel; Silva, Cicero da [UNESP] (Univ Federal Sergipe, 2022)
Distance learning has been an option to mitigate the global spread of the highly contagious disease, named COVID-19 (coronavirus), and declared a Pandemic by the World Health Organization (WHO) in March 2020. Social confinement as a public health strategy to address the health crisis has led to the adoption of new teaching methods in the new social sphere. Higher education contexts have gradually incorporated the opportunities offered by information and communication technologies (ICT). The purpose of the article is to present some theoretical reflections on the inclusion of the Blended Learning (B-Learning) methodological model in higher education, considering the changes that have occurred in the current situation due to the pandemic. Based on the review of the specialized scientific literature in relation to the integration of ICT in educational environments, the relevance of the advantages of technological tools in blended learning in the current context of the COVID-19 pandemic is recognized, specifically for the doctoral training process.
Keywords: Blended learning; COVID-19 pandemic; Higher education; Information and communication technologies